Characterization of the synthetic biology-inspired implementation of a materials-based positive feedback loop - Hanna J. Wagner; Raphael Engesser; Kathrin Ermes; Christian Geraths; Jens Timmer; Wilfried Weber (Data in Brief, 2018)
The translation of engineering designs to materials sciences by means of synthetic biological tools represents a novel concept for the development of information-processing materials systems. Here, we provide data on the mathematical model-guided implementation of a biomaterials-based positive feedback loop for the detection of proteolytic activities. Furthermore, we present data on an extended system design for the detection of the antibiotic novobiocin.This work is related to the research article “Synthetic biology-inspired design of signal-amplifying materials systems” (Wagner et al., 2018) [1]. Keywords: Information-processing, Protease, Signal amplification, Smart materials, Stimulus-responsive